Optimal large‐scale CD34+ enrichment from a leukapheresis collection using the clinimacs prodigy platform. Issue 12 (18th August 2020) - Pello, Oscar M.; Lanzarot, Diego; Colorado, Mercedes; Amunarriz, Cristina; Insunza, Andrés; Álvarez‐Rodríguez, Lorena; Díez de Velasco, María; Sainz‐Sainz, Natividad; Arroyo, José Luis
Abstract: Optimization of Hematology Patient's treatment: It is possible to obtain a 100% CD34+ recovery after CD34+ selection using the CliniMACS Prodigy. Abstract : Optimization of Hematology Patient's treatment: It is possible to obtain a 100% CD34+ recovery after CD34+ selection using the CliniMACS Prodigy.